Serratus Anterior Fascia Free Flap for Functional Surgery of Subungual Melanoma: Case Series and Literature Review - Soo Jin Woo; Sung Tack Kwon; Byung Jun Kim (Archives of Plastic Surgery)
Background In addressing subungual melanoma, this study presents the efficacy of wide excision followed by reconstruction using a serratus anterior fascial free flap.